Bone Morphology in 46 BXD Recombinant Inbred Strains and Femur-Tibia Correlation. (25th February 2015) - Zhang, Yueying; Huang, Jinsong; Jiao, Yan; David, Valentin; Kocak, Mehmet; Roan, Esra; Di'Angelo, Denis; Lu, Lu; Hasty, Karen A.; Gu, Weikuan
Abstract : We examined the bone properties of BXD recombinant inbred (RI) mice by analyzing femur and tibia and compared their phenotypes of different compartments. 46 BXD RI mouse strains were analyzed including progenitor C57BL/6J (n = 16 ) and DBA/2J (n = 15 ) and two first filial generations (D2B6F1 and B6D2F1). Strain differences were observed in bone quality and structural properties (P < 0.05 ) in each bone profile (whole bone, cortical bone, or trabecular bone). It is well known that skeletal phenotypes are largely affected by genetic determinants and genders, such as bone mineral density (BMD). While genetics and gender appear expectedly as the major determinants of bone mass and structure, significant correlations were also observed between femur and tibia. More importantly, positive and negative femur-tibia associations indicated that genetic makeup had an influence on skeletal integrity. We conclude that (a) femur-tibia association in bone morphological properties significantly varies from strain to strain, which may be caused by genetic differences among strains, and (b) strainwise variations were seen in bone mass, bone morphology, and bone microarchitecture along with bone structural property.